Setting an agenda for critical accounting research in the [sic] Barbados and the Eastern Caribbean - Dick-Forde, Emily (2002)
Offers critical accounting theory (CAT) as a way forward for researching accounting in the Caribbean. Argues that the deployment of CAT can result in cutting edge research that is in step with international trends and that provides much needed detail for policy decision making on corporate accounting and reporting practices in the region. Reports on a study where critical accounting was used to investigate and analyze environmental accounting in the Caribbean.